Gender Controversy in Islamic Education Management (Policy Trends and Inclusion Solutions) - Alfarizi, Salman; Mutmainnah, Mutmainnah; Faizah, Nur (JUMPA : Jurnal Manajemen Pendidikan, 2024)
This research aims to explore the strengthening of the role of social institutions in women's empowerment and increasing gender equality. The research method used is mixed-method, combining qualitative and quantitative approaches. Data was collected through observations, in-depth interviews, surveys, and Focus Group Discussions (FGDs) with women aged 15-50, leaders of social institutions, and government officials. The results show that education and training programs organized by social institutions have significantly increased skills, economic independence, and awareness of women's rights. However, cultural resistance and gaps in educational facilities are still major challenges in the implementation of gender equality programs. The implications of this study emphasize the importance of community-based inclusive strategies to overcome cultural resistance and the need for long-term evaluation of women's empowerment programs. In addition, increased collaboration between social institutions, governments, and the private sector is encouraged to ensure the sustainability and effectiveness of these programs